Lesiones tisulares crónicas en ratones blancos inmunizados e infectados con Trypanosoma cruzi - Pérez Reyes, Rodolfo (Universidad de Costa Rica, 1993)
Mice were immunized with whole membranes of cultured epimastygotes and then innoculated with cultured tripomastygotes. The blood parasite count was lower than in the control. No changes could be detected however, in the lenght of the prepatent period nor in the extent and duration of the tissue damage observed in the chronic phase of the infection. Damage was evident in the tissues of both immunized and naive animals up tu 171 days post inoculum. Blood parasites could be demonstrated neither by direct observation nor by culture, as soon as 117 days alter infection. The presence of mast cells a few hours alter infection and throughout the sludy suggests a role of these cells in both the specific and noospecific components of host response